2014
DOI: 10.1002/2013gc005157
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mineral composition and heterogeneity on the reservoir quality evolution with CO2 intrusion

Abstract: During the diagenesis of rocks in a sedimentary basin, an intrusion of CO 2 could cause dissolution or/and precipitation of the surrounding rocks. As a result, the reservoir quality may be altered. The mineral composition and heterogeneity have pronounced impacts on the geochemical reaction and reservoir quality evolution. A numerical simulation method is employed to investigate the influences of primary mineral on the diagenesis. Based on the measured data from the Songliao Basin, a total of 26 two-dimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 66 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…The pore space is filled with residually trapped sc-CO 2 surrounded by CO 2 -saturated water forming a low-pH environment. The magnitude of carbonate mineral trapping capacity is dependent on the formation water composition and the variety of reactive minerals within a reservoir (Gilfillan et al, 2009;Xu et al, 2005;Yang et al, 2014).…”
Section: Processes Controlling the Chemistry At Co 2 -Water-rock Interfacesmentioning
confidence: 99%
“…The pore space is filled with residually trapped sc-CO 2 surrounded by CO 2 -saturated water forming a low-pH environment. The magnitude of carbonate mineral trapping capacity is dependent on the formation water composition and the variety of reactive minerals within a reservoir (Gilfillan et al, 2009;Xu et al, 2005;Yang et al, 2014).…”
Section: Processes Controlling the Chemistry At Co 2 -Water-rock Interfacesmentioning
confidence: 99%
“…Each geothermal field has a unique geological setting and reservoir characteristic [28][29][30]. It might be complicated to determine the "optimal" water reinjection [31,32], but the study of the effect of temperature and acidification on the water-rock interaction can provide a reference for reinjection of the sandstone geothermal reservoir.…”
Section: Implications For Sandstone Reinjection Blockage Reductionmentioning
confidence: 99%
“…Similarly, Yang et al . found that ankerite and kaolinite will precipitate at the expense of chlorite and anorthite dissolution, when investigating the effects of primary mineral abundances on water–rock–CO 2 interaction by modeling . What is more, Choi et al .…”
Section: Introductionmentioning
confidence: 95%
“…6 Similarly, Yang et al found that ankerite and kaolinite will precipitate at the expense of chlorite and anorthite dissolution, when investigating the effects of primary mineral abundances on water-rock-CO 2 interaction by modeling. 7 What is more, Choi et al recorded the precipitation of siderite as a result of chlorite dissolution in a CO 2 injection model, and highlighted the stability of siderite, which is quite sensitive to the dissolution rate of chlorite. 8 Apart from the differences in mineral components, the in situ water chemistry also plays a key role in controlling the minerals' alteration.…”
Section: Introductionmentioning
confidence: 99%